SISTEM MONITORING GAS DAN SUHU PADA BIOGAS DIGESTER UNTUK MENINGKATKAN KINERJA KOMPOR - Febrian, Dharma Ekita Putra; Wisaksono, Arief; Anshory, Izza; Jamaaluddin, Jamaaluddin (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2025)
This research aims to design an Internet of Things (IoT)-based monitoring system capable of monitoring the gas and temperature in a biogas digester to improve the operational efficiency of a biogas-fueled stove. The system utilizes a DS18B20 sensor to ensure the fermentation temperature remains optimal and an MQ-4 sensor to detect methane levels. The data collected by the sensors is processed using an ESP32 microcontroller and displayed directly through the Blynk application. This technology is designed to improve stove performance and biogas production and maximize its use as an environmentally friendly renewable energy. Test results show that the system is effective in monitoring parameter changes with a high degree of accuracy, enabling a more optimized fermentation process and efficient use of biogas. The system provides real-time information regarding digester condition and stove performance, thus supporting the improvement of biogas-based energy efficiency. In addition, this technology contributes to the development of sustainable solutions that benefit both households and the industrial sector.